ANALYSIS OF HOUSEHOLD’S POVERTY STATUS IN ACEH 2018 - Anis Naufal; Siskarossa Ika Oktora (Universitas Padjadjaran, 2023)
No poverty is the first goal of the United Nations Sustainable Development Goals. Based on Law Number 11 of 2006, Aceh Province Government receives a Special Autonomy Fund as compensation for achieving a peace agreement between Aceh Province and the Indonesian Government. This Special Autonomy Fund is valid for 20 years from 2008-2027, which is aimed at poverty alleviation. However, Aceh Province is still the 6th highest percentage of the poor province in Indonesia and the highest in Sumatra in 2018. Thus, this study aims to analyze the demographic, social, and economic variables that affect the poverty status of households in Aceh Province in 2018. The result of the research using ordinal logistic regression indicates that the age, the education level, and the working hours of the head of the household negatively affect the poverty status of the household, while the number of the household member has a positive effect on household poverty status. Households with a female head of household and working in the agricultural sector tend to be poorer.